Influence of shoulder diameter on interfacial microstructure and mechanical behavior in dieless friction stir riveting of CP-Copper to 321 stainless steel. (March 2022) - Fan, Guangli; Paidar, Moslem; Mehrez, Sadok; Ojo, Olatunji Oladimeji; Liu, Mingming; Dai, Yan; Mahariq, Ibrahim
Abstract: This study investigated the influence of changes in the tool shoulder diameter on the microstructure, bonding, diffusion, and tensile-shear behaviors of the dieless friction stir rivetted CP-copper/Zn/AISI 321 stainless steel joints. The results reveal that the increase in the shoulder diameter increases the peak temperature, width of the brazed and stir zones, and the tensile-shear load (1944–2429 N) of the joints. The wider tool shoulder produced a good metallurgical/interfacial bonding at the stir zone and restrained upper sheet bulging (USB) effect at the brazed zone of the joint whereas USB-induced sheet separation and lateral unbonded path could not be prevented with the smaller tool shoulder diameter (12 mm). The change of the tool shoulder diameter changes the fracture behavior and the diffusion gradients of Cu from steep to gradual profile due to differences in the friction-induced heat input/temperature. A wider tool shoulder diameter is recommended for defect elimination and improved strength. Highlights: The influence of changes in the tool shoulder diameter on the microstructure and tensile-shear behaviors of the dieless friction stir rivetted CP-copper/Zn/AISI 321 stainless steel joints. A larger area fraction of fine dendrites is found at the brazed zone of the sample produced with a 15 mm tool shoulder diameter. The increase in the tool shoulder diameter improves interfacial bonding and cutback USB-induced sheet separation at the brazed zone. A change of the tool shoulder diameter from 12 to 15 mm improved the tensile-shear load of the joint from 1944 to 2429 N due to good metallurgical bonding.